Blood glucose reduction associated with wholewheat noodle diet in rats with type 2 diabetes mellitus - Li Wu; Shiyuan Deng; Chunhong Tang; Haijun Chang; Huan You; Shuai Zhang; Ruiping Gao; Chengyao Liu (Scientific Reports)
Abstract The blood glucose reducing effects of wholewheat noodles in a type 2 diabetes mellitus (T2DM) rat model were investigated. The T2DM model was established by feeding the rats a high-fat diet and injection of streptozotocin solution. Three treatment groups were used, in which the model rats were fed low-, medium-, or high-fiber wholewheat noodles (LF, MF, and HF, respectively). Fasting blood glucose, the organ coefficient, oxidative stress, pathological changes, and intestinal microbiota were examined. The wholewheat noodles reduced blood glucose, with the high-fiber diet achieving the greatest effect. Wholewheat noodle intake increased total antioxidant capacity as well as superoxide dismutase, glutathione peroxidase, and catalase activity in the liver and reduced malondialdehyde content. Increasing the fiber content increased intestinal microbiota species richness and diversity and improved intestinal microbiota composition. The wholewheat diets were associated with upregulated gene expression of insulin receptor, insulin receptor substrate 2, and glucose transporter 2 and of the downstream signaling molecules protein kinase B and 3-phosphoinositide-dependent kinase 1. The wholewheat diet downregulated phosphatidylinositol-3-kinase (PI3K) regulatory subunit p85 gene expression and in turn enhanced insulin-activated PI3K signaling and glucose uptake and utilization in liver tissues, thus reducing blood glucose. Therefore, the blood glucose reducing effects of wholewheat noodles increase as their fiber content increases.